THE EFFECTIVENESS OF COMBINATION OF KANGAROO MOTHER CARE METHOD AND LULLABY MUSIC THERAPY ON VITAL SIGN CHANGE IN INFANTS WITH LOW BIRTH WEIGHT - Nuuva Yusuf; Suharyo Hadisaputro; Runjati Runjati; Ari Suwondo; Imam D Mashoedi; Supriyana Supriyana (Belitung Nursing Journal, 2017)
Background: Kangaroo mother care (KMC) and lullaby music methods have been considered as the alternative treatment for vital sign changes in low birth weight infants. However, little is known about the combination of the two methods. Objective: To identify effectiveness of combinations of Kangaroo mother care and Lullaby music methods on changes in vital signs in low birth weight infants. Methods: A quasi experiment with non-equivalent control group design. This study was conducted on October– December 2016 at the General Hospital of Ambarawa and General Hospital of Ungaran, Semarang, Indonesia. There were 36 samples selected using consecutive sampling divided into three groups, namely: 1) a group of low birth weight infants with the combination of KMC and lullaby music, 2) an low birth weight infant group with the lullaby music intervention, and 3) a control group given standard care in low birth weight infants by KMC method. Paired t-test and MANOVA test were used to analyzed the data. Results: Findings revealed that there were significant differences between the combination group, lullaby music group, and control group in temperature (p=0.003), pulse (p=0.001), respiration (p=0.001), and oxygen saturation (p=0.014) with significant value of <0.05, which indicated that there was a statistically significant difference in vital sign changes among the three groups. Conclusion: The combination of KMC method and lullaby music intervention was effective on vital sign changes (temperature, pulse, respiration, and oxygen saturation) compared with the lullaby music group alone and control group with KMC method in low birth weight infants. It is suggested that the combination of KMC and lullaby music methods can be used as an alternative to improve low birth weight care for mothers in the NICU and at home and to reach the stability of the baby's vital signs.